Технология переработки нефти и газа: учебное пособие - Ивашкина Е. Н. Елена Николаевна; Юрьев Е. М. Егор Михайлович; Кривцова Н. И. Надежда Игоревна; Белинская Н. С. Наталия Сергеевна (Томск, Изд-то ТПУ, 2021)
Заглавие с титульного экрана